2015
DOI: 10.1039/c4ra16866f
|View full text |Cite
|
Sign up to set email alerts
|

A facile route for the synthesis of mesoporous melamine-formaldehyde resins for hexavalent chromium removal

Abstract: A facile route for the synthesis of mesoporous melamine-formaldehyde resins (MMF) for hexavalent chromium removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…The SEM image (Figure b) revealed that MMF@Fe 3 O 4 had a uniform distribution, while no large‐size Fe 3 O 4 particles were detected, suggesting a complete inclusion of Fe 3 O 4 particles in the MMF@Fe 3 O 4 composite. The nitrogen sorption isotherm of MMF@Fe 3 O 4 (Figure c) exhibited a typical type IV curve with a hysteresis loop at a relative pressure of 0.40–0.90, which confirmed the presence of mesoporosity in MMF@Fe 3 O 4 . As shown in Figure d, the pore size of MMF@Fe 3 O 4 revealed a broad range from 2 to 25 nm and centered at 5.84 nm, which was calculated using the Barrett–Joyner–Halenda method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SEM image (Figure b) revealed that MMF@Fe 3 O 4 had a uniform distribution, while no large‐size Fe 3 O 4 particles were detected, suggesting a complete inclusion of Fe 3 O 4 particles in the MMF@Fe 3 O 4 composite. The nitrogen sorption isotherm of MMF@Fe 3 O 4 (Figure c) exhibited a typical type IV curve with a hysteresis loop at a relative pressure of 0.40–0.90, which confirmed the presence of mesoporosity in MMF@Fe 3 O 4 . As shown in Figure d, the pore size of MMF@Fe 3 O 4 revealed a broad range from 2 to 25 nm and centered at 5.84 nm, which was calculated using the Barrett–Joyner–Halenda method.…”
Section: Resultsmentioning
confidence: 99%
“…MF contains abundant nitrogen atoms, which can well coordinate with transition metals . However, studies of enrichment and detection of metal ions using MF are scarce . Lv et al designed and synthesized magnetic mesoporous MF nanoparticles to adsorb Cr(VI), which showed high adsorption capacity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,9] This kind of pollution has become an epidemic problem so the removal of HMIs is a major issue in world. [10] To date, several approaches were applied to remove the HMIs from water including nanofiltration, membrane separation, ion exchange, [11,12] resin, [13] photocatalytic degradation, [14] chemical moisture, membrane filtration, freezing, chemical deposition, biological treatment, reverse osmosis, adsorption, etc. [15][16][17][18][19][20] Adsorption is one of the best treatment methods because it does not require high temperatures, as well as several substances, that can be captured at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks based on Cu-benzenetricarboxylates have been used for the adsorption of Cr(VI) from aqueous solution, whose maximum adsorption capacity was 48 mg g À1 . 8 BaTiO 3 @SBA-15 nanocomposite was used as an adsorbent for the removal of Cr(VI)-contaminated water and it showed an adsorption capacity of 98.2 wt% within only 40 min contact time in a batch reactor. 7 A highly mesoporous melamine-formaldehyde resin showed enhanced adsorption capacity (66.65 mg g À1 ) and selectivity for Cr(VI).…”
Section: Introductionmentioning
confidence: 99%